Pengaruh Tıngkat Pendidikan, Pelatihan, Pengalaman Kerja terhadap Kinerja Pemeriksa Pajak pada Kanwil DJP Riau dengan Kompensasi Finansial sebagaı Variabel Pemoderasi - Fitriani Fitriani; Vince Ratnawati; Alfiati Silfi (Jurnal Ekonomi, 2019)
The objectives of this research are to investigate the effect of education levels, training, work experience on the tax examiners performance at the regional office of directorate general of taxes Riau. This study also investigate the moderating role of Financial Compensation. The data were obtained from a questionnaire and the samples 147 respondens who are tax examiners in Regional Office of Directorate General of Taxes Riau. Data processed using multiple linear regression analysis and moderate regression analysis of IBM SPSS Version 21. The results showed that the level of education, training, work experience affect the performance of tax examiners at the Regional Office of Directorate General of Taxes Riau with Pvalue < alpha 0.05 value of 0.000, 0.002, 0.000. Financial compensation moderates the effect of education and work experience on the performance of tax examiners with Pvalue < alpha 0.05 values of 0.030 and 0.026. However, financial compensation does not moderates the effect of training on the performance of tax examiners with Pvalue > 0.05, values of 0.243.